Interaction of isolated cross-linked short actin oligomers with the skeletal muscle myosin motor domain - Qu, Zheng; Fujita-Becker, Setsuko; Schröder, Rasmus R. (The FEBS journal, 2018)
The cyclical interaction between F-actin and myosin in muscle cells generates contractile force. The myosin motor domain hydrolyses ATP, resulting in conformational changes that are amplified by the myosin lever arm that links the motor domain to the rod domain. Recent cryo-electron microscopic data have provided a clear picture of the myosin-ATP-F-actin complex, but structural insights into other stages of the myosin-actin interaction have been less forthcoming. To address this issue, we cross-linked F-actin subunits between Cys374 and Lys191, and separated them by gel filtration. Purified actin-dimers, -trimers and -tetramers retained the ability to polymerize and to stimulate myosin-subfragment 1 (myosin-S1) ATPase activity. To generate stable actin oligomer:myosin-S1 complexes, we blocked actin polymerization with gelsolin and Clostridium botulinum iota toxin-mediated ADP-ribosylation. After polymerization inhibition, actin-trimers and -tetramers retained the ability to stimulate the myosin-S1-ATPase, whereas the actin-dimer showed very little ATPase stimulation. We then analysed the stoichiometry and binding affinity of myosin-S1 to actin oligomers. Actin-trimers and -tetramers bound myosin-S1 in the absence of nucleotide; the trimer contains one myosin-S1 binding site. We calculated a dissociation constant (Kd) of 1.1 × 10−10 m and 1.9 × 10−10 m for binding of native F-actin and the actin-trimer to myosin-S1, respectively. EM of the actin-trimer:myosin-S1 complex demonstrated the presence of single particles of uniform size. Image reconstruction allowed a reasonable fit of the actin-trimer and myosin-S1 into the obtained density clearly showing binding of one myosin-S1 molecule to the two long-pitch actins of the trimer, supporting the kinetic data.
Gesehen am 18.05.2020